Second trimester rupture of an unscarred uterus following blunt trauma: a case report - Mathews, Basil; T., Chitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Uterine rupture is a life-threatening emergency in obstetrics carrying an increased risk of maternal and foetal morbidity and mortality. Often, uterus ruptures during labour; however, scarred uterus may rupture before the onset of contractions in the late third trimester. Uterine rupture in an unscarred uterus occurs extremely rare. Various aetiology has been described in literature from anomalous uterus, uterine manoeuvres, and abnormal placentation to congenital exposure to Diethylstilbestrol. Maternal outcome depends greatly on the early diagnosis, prompt management and availability of emergency expert care and blood transfusion. However, the diagnosis is not always obvious with its varied non-specific presentation. Most common presentation of rupture uterus is acute abdomen, which is often mistaken for other causes like acute pancreatitis, appendicitis, cholecystitis, especially in the early pregnancy. Authors report a case of grand multipara at 19 weeks of gestation presented as acute abdomen. She was referred as incomplete abortion in need of blood transfusion, later diagnosed to be rupture of uterus. She had abdominal pain and vaginal bleeding for 14hours duration prior to admission. On further inquiry, history of blunt trauma to abdomen, the day prior was revealed.